Physical education for learning: A guide for secondary schools - Lloyd, Rebecca J.; Garcia Bengoechea, Enrique; Smith, Stephen J. (Université d'Ottawa | University of Ottawa, 2010)
A key measure of teacher effectiveness is certainly that of student engagement. Yet engaged students need also to be learning something substantial, meaningful and long-lasting. In other words, the focus of learning, which is framed by the curriculum, needs to be considered carefully along with how things are learned, which is a process of gaining knowledge, skills and dispositions via instructional intent. Learning theories guide our considerations of what should be learned in Physical Education and how targeted knowledge, skills and dispositions can be best acquired by having us examine prior questions about what is worth knowing. These theories, as we shall see, help us pinpoint the kind of learning that is distinctive to Physical Education and the instructional means of enhancing such learning.
Keywords: What Is Learning; Cognitive Learning Perspective; Situated Learning Perspective; Organic Approach to Learning